PENENTUAN KUALITAS PROTEIN BERDASARKAN KANDUNGAN ASAM AMINO PADA BULU BABI (Tripneustes gratilla Linnaeus) - Feronika Floren Fraulaine; Maik NR Akobiarek (Universitas Cenderawasih, 2016)
This research, â€œThe Determination of Protein Quality According To Amino Acid in Sea Urchin (Tripneustes Gratilla Linnaeus)â€, was conducted from July toÂ November 2016. It aims to find out the protein quality based on amino acid which contained in sea urchin. This research was carried out at Laboratorium Terpadu Institut Pertanian Bogor with the use of High Performance Liquid Chromatography (HPLC) and Asam Amino Analyzer (AAA) as the method to discover the amino acid. The result indicated that the level of pig-based gonad protein based on dry weight was 46,25 % b/b, and contained 16 types of amino acids. Ten essential amino acids (Histidine, Leucine, Isoleucine, Methionine, Phenylalanine, Lysine,Â Treonin, Tryptophan, Valine, and Arginine), and six non-essential amino acids(Aspartic Acid, Glutamate Acid, Serine, Glisin, Alanine, Tyrosine). The protein quality based on the type and proportion of amino acids containing in gonads was high-quality protein, where the score of the gonad's amine gonadwas 34%. It was determined in accordance with the comparison of the lowest essential amino acids in the fur gonad with the same essential amino acid proteinÂ standard. The lowest amino acid or barrier on gonads of sea urchins was Tryptophan.Keywords: Quality Protein, Essential Amino Acids, Amino Acid Scores, Limiting AminoÂ Acids, Gonads of Sea Urchins